2016
DOI: 10.3390/toxins8060183
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Snake Venom Metalloproteinases: Generation of Toxin Diversity and Enzyme Inactivation

Abstract: Snake venom metalloproteinases (SVMPs) are abundant in the venoms of vipers and rattlesnakes, playing important roles for the snake adaptation to different environments, and are related to most of the pathological effects of these venoms in human victims. The effectiveness of SVMPs is greatly due to their functional diversity, targeting important physiological proteins or receptors in different tissues and in the coagulation system. Functional diversity is often related to the genetic diversification of the sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 103 publications
(138 reference statements)
1
21
0
2
Order By: Relevance
“…This process controls the activation state of enzymes by blocking the catalytic site (inactivated state) and proteolytic processing of the prodomain (active state) 79 81 . As showed in previous studies 82 84 the prodomains of the SVMPs are cleaved after maturation in the Golgi complex or as soon as they reach the lumen of the venom gland. Our proteomic data did not identify any peptide belonging to the prodomain site (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 52%
“…This process controls the activation state of enzymes by blocking the catalytic site (inactivated state) and proteolytic processing of the prodomain (active state) 79 81 . As showed in previous studies 82 84 the prodomains of the SVMPs are cleaved after maturation in the Golgi complex or as soon as they reach the lumen of the venom gland. Our proteomic data did not identify any peptide belonging to the prodomain site (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 52%
“…In the present work, three types of posttranslational modification were also observed, i.e., N-terminus pyro-glutamate, methionine oxidation and N-terminal acetylation (N-ace). Pyro-glutamate posttranslational modifications of the venom proteins has been described before and are known to confer stability to the proteins and peptides [ 52 , 53 , 54 , 55 ]. However, modification of methionine residues and pyro-glutamate cannot be excluded during sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the different kinds of cnidarian metalloproteinases and their effects are not yet clear. It has been demonstrated that SVMPs undergo various post-translational modifications, which contribute to their great functional diversity ( Moura-da-Silva et al, 2016 ). This could be the case of cnidarian metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%